Pengembangan Media Pembelajaran Fisika Berbasis Animasi komputer Untuk Sekolah Menengah Atas Berbasis Macromedia Flash 8 - Arif Rahman Aththibby (Jurnal Pendidikan Fisika, 2014)
The research was motivated by the learning process of physics is less interest, but phyisics learning will be easier to accepted with students if the learning process is packed more interesting. This study aimed to make the physics learning media based computer animation  from the topic of Newton laws used software Macromedia Flash 8,and to know the validation of physics learning media based computer animation.  This media was conducted by ADDIE model. The result of this study showed that: 1) it has been made the physics learning media based computer animation, 2) general assesment of the obtained result are very good products, making it feasible to use in their  physics lesson in senior high school,.